Implementation of telesoftware software feature in teletext system - Tan, Jek Thoon. (2008)
Telesoftware is a generic name for extracting Teletext data to run user application. In this project, a method of downloading program codes to the TV receiver using the Teletext transmission system is investigated. The downloaded program codes can be used to run value-added services such as game applications or electronic program guides using available Teletext decoder resources. In Telesoftware implementation, a means of downloading the "program codes" is realised by extracting the Teletext data from the composite video signal and stored in the Teletext decoder system. When downloading of the program data or code is completed, a call or jump instruction can be initiated to move the microcontroller program counter to the start of the downloaded program code area to run the Telesoftware features. This report delves on the Telesoftware development. It describes both hardware and software implementation details enabling Telesoftware feature realisation. A dedicated Text microcontroller (Philips 8XC652) is used and the firmware for implementing Telesoftware is developed. The microcontroller 8XC652 is a derivative of the widely used embedded controller Intel 80C51. It has dedicated I2C interfaces and has the same instruction set as 80C51. This report delves into concept and implementation details of the Telesoftware feature and a set of protocols enabling Telesoftware realisation is defined.